ACCELERATED PRODUCTION OF VIRUS-FREE POTATO PLANTING MATERIAL USING A BIOREACTOR - Dmitriy Vladimirovich Volkov,; Assel Mukhtarkyzy Argynbayeva,; Dias Lamzarovich Daurov,; Kuanysh Kabyluly Zhapar,; Zhandos Sailaubekuly Abai,; Kabyl Zhaparovich Zhambakin,; Malika Khabidulayevna Shamekova, (Academic Journal of Physical and Chemical Sciences, 2020)
Potato production is one of the key branches of crop production that determines the food security of Kazakhstan. The Republic needs over 800,000 tons of seed potatoes per year. In addition to seed potatoes, which are grown in Kazakhstan, about 30,000 tons of seed potatoes are imported annually, while about 80% of this volume is imported from the Netherlands through private companies [1]. In 2018, 193.0 thousand hectares were occupied under potatoes in Kazakhstan, while the gross harvest amounted to 3806.9 thousand tons. At the same time, the yield in 2018 was only 19.8 t/ha. While in neighboring Uzbekistan in 2018, the yield was 33.68 t/ha, the maximum yield in New Zealand in 2018 was about 50.41 t/ha[2]. It is known that one of the main reasons for low potato yield is low-quality seed material. In Kazakhstan, mainly after obtaining virus-free plants in vitro through meristem culture, minitubers are obtained from them in most technological processes; in rare cases, microtubers are obtained from meristem plants in vitro and then minitubers from them. Research has shown that the bioreactor can massively clone meristem plants and get full-fledged virus-free microtubules reducing a significant proportion of manual labor, thereby reducing the impact on the result of the human factor, reduce infections, and reduce labor costs and material costs.